\[\boxed{\text{423\ (423).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[m = 11x + 9;\ \ n = 11y + 5:\]
\[mn = (11x + 9) \cdot (11y + 5) =\]
\[= 121xy + 55x + 99y + 45 =\]
\[= 11 \cdot (11xy + 5x + 9y) + 45.\]
\[11 \cdot (11xy + 5x + 9y) -\]
\[делится\ на\ 11;\]
\[45\ :11 = 4\ и\ остаток\ 1.\ \]
\[Что\ и\ требовалось\ доказать.\]
\[\boxed{\text{423.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)* - \left( 3x^{2} - 4xy + 2y^{2} \right) =\]
\[= 9x^{2} + y^{2}\]
\[*\ =\]
\[= 9x^{2} + y^{2} + \left( 3x^{2} - 4xy + 2y^{2} \right)\]
\[*\ =\]
\[= 9x^{2} + y^{2} + 3x^{2} - 4xy + 2y^{2}\]
\[*\ = 12x^{2} - 4xy + 3y^{2}.\]
\[2)\ a^{3} - 6a^{2} + 2a - (*) =\]
\[= a^{5} + 2a^{2} - 7\]
\[*\ =\]
\[= a^{3} - 6a^{2} + 2a - \left( a^{5} + 2a^{2} - 7 \right)\]
\[*\ =\]
\[= a^{3} - 6a^{2} + 2a - a^{5} - 2a^{2} + 7\]
\[*\ = - a^{5} + a^{3} - 8a^{2} + 2a + 7\]